(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Anxiety is one of the important variables that can effect on the present and future life of children.The aim of this study was to predictchildren's anxiety through Corona Disease Anxiety and Parental Stress during coronavirus quarantine. The research method wascorrelational. The study statistical population was all primary children and their mothers of Ahwaz in the year 2019-20. Out of 400eligible mothers, 300 mothers were selected as the sample by convenience sampling method and answered online the questionnairesincluding Corona Disease Anxiety Scale, short form of Parental Stress Questionnaire and Spence Children’s Anxiety Scale- ParentVersion. The Mothers completed Corona Disease Anxiety Scale, short form of Parental Stress Questionnaire and Spence Children’sAnxiety Scale- Parent Version. Pearson correlation coefficient and stepwise regression were used to analyze the data.. The resultsindicated that there is a positive and significant correlation between corona disease anxiety and parenting stress with children's anxietyduring coronavirus quarantine . Also, the results of regression analysis showed that corona disease anxiety and parenting stress cansignificantly predict 31% of changes in children's anxiety. Therefore, it is suggested that the necessary planning be done to reduce theanxiety of parents and children during epidemics.